2005
DOI: 10.1300/j229v06n03_06
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic Dissociation and Emotions as Predictors of PTSD Symptoms Following Childbirth

Abstract: ABSTRACT. The current study investigated the contributive role of perinatal dissociative and perinatal emotional responses to the development of PTSD symptoms following childbirth. Method: Using a prospective, longitudinal design, 140 women were studied who were followed from the first week after delivery to three months postpartum. Results: Three women (2.1%) met criteria for PTSD and 21.4% reported a traumatic childbirth experience. Both perinatal negative emotional reactions and perinatal dissociative react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
2
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 39 publications
5
93
2
12
Order By: Relevance
“…This is consistent with research in obstetric and other trauma samples suggesting dissociation may be an early marker for the development of PTSD (Olde, et al, 2005;Van der Velden, et al, 2006;Van Son, Verkerk, Van der Hart, Komproe, & Pop, 2005). For example, Olde et al, (2005) found that intrapartum psychoform dissociation and somatoform dissociation were strongly related to PTSD symptoms three months after birth, even after controlling for negative emotions during birth. Dissociation is a broad concept that can describe symptoms, a process, or a pattern of personality organisation (Vermetten, Dorahy, & Spiegel, 2007).…”
Section: Cognitions Emotions and Dissociation During Hotspotssupporting
confidence: 85%
“…This is consistent with research in obstetric and other trauma samples suggesting dissociation may be an early marker for the development of PTSD (Olde, et al, 2005;Van der Velden, et al, 2006;Van Son, Verkerk, Van der Hart, Komproe, & Pop, 2005). For example, Olde et al, (2005) found that intrapartum psychoform dissociation and somatoform dissociation were strongly related to PTSD symptoms three months after birth, even after controlling for negative emotions during birth. Dissociation is a broad concept that can describe symptoms, a process, or a pattern of personality organisation (Vermetten, Dorahy, & Spiegel, 2007).…”
Section: Cognitions Emotions and Dissociation During Hotspotssupporting
confidence: 85%
“…Furthermore, it is unclear whether our results can be generalized to types of trauma from other than man-made disasters (see, for instance, the results on childbirth stress by Olde et al, 2005). Potential risk factors such as peritraumatic dissociation may not be equivalent across different types of trauma (Brewin, Andrews, & Valentine, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…6. We excluded general studies on childbirth (Olde, Van der Hart, Kleber, van Son, Wijnen, & Pop, 2005) but included studies with respect to pregnancy loss because of the stressor criterion of the PTSD diagnosis (criterion A, DSM-IV).…”
Section: Methodsmentioning
confidence: 99%